Iron species and sulfur isotopic compositions of authigenic pyrite in deep-sea sediments at southern Hydrate Ridge, Cascadia margin (ODP Leg 204): implications for non-steady-state depositional and diagenetic processes - Liu, Chenhui; Jiang, Shao-Yong; Su, Xin; Bian, Xiaopeng; Ding, Hai; Li, Da; Yang, Tao (Frontiers in Marine Science, 2024)
Two accretionary sediment sequences from Sites 1245 and 1252 recovered during Ocean Drilling Program (ODP) Leg 204 at southern Hydrate Ridge were investigated to explore the response of geochemical partitioning of iron and sulfur isotopic composition of authigenic pyrite to non-steady-state depositional and diagenetic scenarios. Five iron species were characterized by a modified sequential extraction procedure that covers almost all iron-bearing minerals in sediment cores, including: (1) iron-bearing carbonates, mainly siderite; (2) ferric (hydr)oxides, probably ferrihydrite and/or lepidocrocite; (3) magnetite; (4) iron-bearing silicates; and (5) pyrite. Highly reactive iron has been accumulated for a long-term steady-state history and its pyritization, to varying degrees, is limited by availability of dissolved sulfide. This causes pyrite and siderite occurred in the same sedimentary layer and shows an inverse relationship between their concentrations. From this, their proportions to highly reactive iron can be chosen for evaluating the degree of sulfidization. A significant change in sulfur isotopic composition of pyrite (-42.4 to +16.8‰ VCDT) indicates that the steady-state conditions are dramatically limited, where the δ34S values higher than -20‰ may result from an upward shift of SMT zone close to the seafloor or a sudden, massive depositional event. To explain the downcore sulfidization effects and pyrite δ34S values, we developed two categories of conceptual scenarios based on variations in sedimentation rate and methane flux. The geochemical features similar to those derived from each scenario were searched in the sediment columns and the non-steady-state events behind the scenarios were proved to be consistent with the real observations. Thus, iron species and pyrite δ34S values can be regarded as a proxy to differentiate different non-steady-state depositional and diagenetic controls on the sedimentary record.